Գլաձորի համալսարանը և Վերին Նորավանքի դպրոցը - Մաթևոսյան, Կարեն
The University of Gladzor operated in Vayots‘ Dzor Province in 1282-1338 under the patronage of the Khaghbakean (Pṛosh‘ean) princes and left a rich cultural heritage. It was believed that the school of the Verin Noravank‘ Monastery in the same province, originated from Gladzor; however, the facts show that this school was founded in the 1290s and operated under the patronage of the Orbelean princes. The Verin Noravank‘ School was headed by vardapet David, who worked in close cooperation with Gladzor University. The next head of the school was vardapet Kiwrion, who was last mentioned in 1360. The activity of the Verin Noravank‘ School continued until the end of the 15th century. This monastery is now known as Shativank‘ or Shatik Monastery, a name it received after reconstruction in the 1750s. Гладзорский университет действовал в провинции Вайоц Дзор в 1282- 1338 гг. под покровительством князей Халбакян (Прошян), и оставил богатое культурное наследие. Считалось, что школа монастыря Верин Нораванк (в той же провинции), берет свое начало от Гладзора, однако факты свидетельствуют, что школа Верин Нораванк была основана в 1290-х годах и действовала под покровительством князей Орбелян. Школу Верин Нораванка возглав- лял вардапет Давид, который работал в тесном сотрудничестве с Гладзорским университетом. Следующим главой школы стал вардапет Кюрион, последний раз упоминавшийся в 1360 году. Деятельность школы Верин Нораванка продолжалась до конца 15 века. Этот монастырь сейчас известен как Шативанк или монастырь Шатик. Это название он получил в 50-х годах XVII века после реконструкции.
Keywords: Ձեռագրական մշակույթ